Fibulin‐4 as a potential extracellular vesicle marker of fibrosis in patients with cirrhosis - Masaru Kumagai; Atsunori Tsuchiya; Yuan Yang; Nobutaka Takeda; Kazuki Natsui; Yui Natusi; Kei Tomiyoshi; Fusako Yamazaki; Yohei Koseki; Hiroki Shinchi; Naoko Imawaka; Ryo Ukekawa; et al. (FEBS Open Bio, 2024)
Chronic liver injury leads to decreased liver function and increased fibrosis. Fibrosis is not only associated with the development of portal hypertension and carcinogenesis, but with the occurrence of events and a poor prognosis, highlighting the importance of non‐invasive fibrosis assessment in patients. In the present study, we searched for markers related to liver fibrosis via proteomic analysis of small extracellular vesicles (sEVs). In the discovery cohort, proteomic analysis was carried out in the sEVs extracted from the sera of 5 patients with decompensated cirrhosis, 5 patients with compensated cirrhosis, and 5 controls without liver disease. Interestingly, in this cohort, fibulin‐4 was significantly associated with cirrhosis while in the validation cohort [formed by 191 patients: 7 patients without disease, 16 patients without liver disease (other diseases), 38 patients with chronic liver disease (CLD), 75 patients with cirrhosis of Child–Pugh class A (36 without hepatocellular carcinoma [HCC], 29 with HCC), and 65 patients with cirrhosis of Child–Pugh class B–C (39 without HCC, 26 with HCC)], fibulin‐4/CD9 levels increased with cirrhosis progression. Furthermore, the fibulin‐4/CD9 ratio was significantly higher in patients with varices. Immunostaining also revealed strong fibulin‐4 expression in cholangiocytes within the fibrous areas and mesothelial cells in liver tissue blood vessels. Taken together, our results suggest that fibulin‐4, essential for lysyl oxidase activation, might be a new liver fibrosis marker found in the sEVs of patients with cirrhosis.